Disaster Management in Smart Cities using IoT and Big Data. Issue 1 (December 2020) - Ramesh, Akil; Rajkumar, S; Jenila Livingston, L M
Abstract: Disasters are the most vulnerable factors which are affecting the human life and environment. Smart cities are mainly affected by disasters. This shows the requirement of an efficient disaster management system in smart cities. This paper deals with disaster management technique used in smart cities to detect disasters like building fire, pollution in atmosphere, route blockage using Big Data Analysis and Internet of Things (IoT). A combination of Hadoop environment is used in disaster reliant smart cities. IoT is used as a front end for collecting real time data sets and Big data analysis for data pre-processing and aggregation. This work evaluates the threshold capacity of each data which is collected for these disasters using Z-score normalization and if collected parameter exceed above the threshold value, then alert message is sent to public service sector such as fire station, police station and hospital. Different challenges faced by this evaluation are discussed in this manuscript.